Weighted likelihood ratio chart for statistical monitoring of queueing systems. Issue 1 (2nd January 2017) - Qi, Dequan; Li, Zhonghua; Zi, Xuemin; Wang, Zhaojun
Abstract : In recent years, effective monitoring of queueing systems has increasingly attracted attention of researchers in the area of statistical process control. Most existing works in the literature, however, did not consider the data autocorrelation, nor rigorously evaluate the performance. In this paper, considering the data autocorrelation, a control chart based on the weighted likelihood ratio test (WLRT) is proposed to efficiently monitor the utilization of queueing systems, particularly the M/M/1 queueing system. Our approach can be readily extended to other general queueing systems if the likelihood function can be obtained. Numerical results and illustrative example show that the performance of the proposed WLRT chart is quite satisfactory.